Media Komunikasi dalam Peran Dakwah - Effendy, Erwan; Karsita, Muhammad Faruq; Harahap, Sylvia Amalia; Syakira, Nayaka; Aini, Azizah; Khairunnisa, Farida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The method of preaching has changed over time. Written sermons are now more important and effective than oral sermons, especially in works that contain preaching messages and social media. This is in line with the saying of the Prophet Muhammad,